Emissões otoacústicas produto de distorção: estudo da função de crescimento em indivíduos com limiares audiométricos normais - Buzo, Byanka Cagnacci (2007)
Introduction: The study of Distortion Product Otoacoustic Emission Input/Output Function (DPOAE I/O) is a very useful instrument to access and to understand the cochlear physiology, specially the mechanism of compression, the cochlear non-linearity and the function of outer hair cells. Therefore, the importance of studies about the possible clinic applications of this test arises. The mechanisms of cochlear physiology still represent an important object of study; consequently, the researches that try to identify the possible clinic applications with the varied kinds of Otoacoustic Emissions (OAE) will result in a relevant development of the audiology area. Objective: To describe the results of the Distortion Product Otoacoustic Emission Input/Output Function (DPOAE I/O) of individuals with regular audiometric thresholds. Method: The DPOAE I/O were researched in the frequencies of 1kHz, 1,5kHz, 2kHz, 3kHz, 4kHz, 5kHz and 6kHz in 104 ears; it should be considered that 44 of these ears were male and 60 of them were female. The level of L2 varied from 45 to 75dBSPL, L1= 0,4*L2 + 39dB, and f1/f2 = 1,22. The equipment used was the ILO 292 USB II with software ILO V6 Otodynamics. Results: The results demonstrated meaningful statistic differences between the DPOAE I/O of the gender in the frequencies of 5kHz and 6kHz, and between the right and the left ears in the frequencies of 3kHz, 4kHz and 6kHz. It is important to note that meaningful statistic differences were also observed between the averages of slopes related to the gender in the frequencies of 5kHz and 6kHz. However, differences related to the age group of the population were not observed. Conclusions: The outcomes of DPOAE I/O and the values of female slopes were higher than the male slopes in the frequencies of 5kHz and 6kHz in both ears. While in the DPOAE I/O of 3kHz, 4kHz and 6kHz there was a tendency of higher outcomes from the right ear than from the left ear. The higher occurrence of absent outcomes in the DPOAE I/O was in the frequency of 6kHz and at the level of L2=45dB. Differences related to the age group of the population were not observed